PENDIDIKAN AGAMA ISLAM DAN ANTISIPASI RADIKALISME KEAGAMAAN - Noor, Wahyudin (Scientia: Jurnal Hasil Penelitian, 2019)
This paper is structured and aims, first, to describe the implementation of Islamic Religious Education in high schools in the Pangkalpinang City, and second, to reveal the implications of the implementation of Islamic religious education in an effort to anticipate the strengthening of religious radicalism in high school students in the Pangkal Pinang City. The results can be explained as follows: 1) the implementation of Islamic religious education in high schools in the Pangkalpinang City generally aims to increase knowledge, convey the teachings and rules of Islamic religion, change morals and foster students according to religious rules and improve practices of worship that have not been good. In terms of material, the books used to refer to books published by the Ministry of Education and Culture and some teachers also complete them with other published books. As for the material presented, the teacher occasionally links, for example, the theory of Islamic education with cultural traditions. 2) Implications of the implementation of Islamic religious education in terms of objectives namely how to minimize the strengthening of the understanding of religious radicalism by studying and applying the values ​​of togetherness, goodness, and general values ​​between religions or certain groups; overall the contents of the study references are from official sources. On the other hand, linking Islamic religious education materials with the culture of society is something that needs to be done to anticipate the spread of religious radicalism in schools; from the method side, there is a reduction in indoctrination patterns.